Pre- and in-hospital mortality for moderate-to-severe traumatic brain injuries: an analysis of the National Trauma Data Bank (2008-2014). (23rd February 2021) - Graves, Whitney C.; Oyesanya, Tolu O.; Gormley, Mirinda; Røe, Cecilie; Andelic, Nada; Seel, Ronald T.; Lu, Juan
ABSTRACT: Objectives : This study aimed to: (1) evaluate pre- and in-hospital mortality for moderate-to-severe TBI in the U.S. by injury type (blunt vs. penetrating) and (2) estimate annual regression-adjusted mortality from 2008-2014. Methods : Data were analyzed from the National Trauma Data Bank (N=247, 648). Multivariable logistic regression analyses were performed by injury type to assess changes in mortality between study periods (early period: 2008–2010; late period: 2011–2014) and to estimate annual regression-adjusted mortality. Mortality odds ratios and 95% confidence intervals were calculated. Results : Total observed mortality was 18.8%. After covariate adjustment, patients in the late period had an increased odds of prehospital mortality compared to patients in the early period for blunt (OR: 4.69; 95%CI: 4.41–4.98) and penetrating trauma (OR: 4.71; 95%CI: 4.39–5.06). In contrast, patients in the late period had a decreased odds of in-hospital mortality compared to patients in the early period for blunt (OR: 0.95; 95%CI: 0.91–0.98) and penetrating trauma (OR: 0.92; 95%CI: 0.85–0.98). Conclusions : The decreasing in-hospital mortality trend is consistent with previous literature. Additional research is warranted to validate the observed increase in prehospital mortality and to identify best practices that can improve prehospital outcomes for patients with moderate-to-severe TBI.